2022
DOI: 10.1371/journal.pone.0262123
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of oral swabs for non-sputum based TB diagnosis in a TB/HIV endemic setting

Abstract: Objective We evaluated diagnostic performance of oral swab analysis (OSA) for tuberculosis (TB) in a high HIV/TB burden setting in Kenya. Methods In this cross-sectional study, buccal swabs and sputum were collected from 100 participants with suspected TB in outpatient clinics in Kenya at enrollment and subsequent morning visits. Buccal swabs underwent IS6110-targeted qPCR analysis. Sputum was evaluated by Xpert MTB/RIF (Xpert) and culture. Diagnostic performance of OSA for TB diagnosis was evaluated relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…Samples must be collected taking medical condition into account, either from the upper (nasal/ throat specimens) or lower respiratory tract (bronchoalveolar lavage fluid, tracheal aspirate). Additionally, improved detection methods are making the use of new types of specimens possible and even saliva and oral mucosa may have a role to play in some situations [43][44][45][46]. But this is not true for all microorganisms, it depends on the pathogenesis and whether they are primary pathogens or potentially commensal.…”
Section: Appropriate Sample and Methodologymentioning
confidence: 99%
“…Samples must be collected taking medical condition into account, either from the upper (nasal/ throat specimens) or lower respiratory tract (bronchoalveolar lavage fluid, tracheal aspirate). Additionally, improved detection methods are making the use of new types of specimens possible and even saliva and oral mucosa may have a role to play in some situations [43][44][45][46]. But this is not true for all microorganisms, it depends on the pathogenesis and whether they are primary pathogens or potentially commensal.…”
Section: Appropriate Sample and Methodologymentioning
confidence: 99%
“…4,6 Oral swabs taken from the buccal or tongue mucosa are being assessed for TB detection. 7 However, in children, optimization of commercial nucleic acid amplification tests (NAATs) is needed as the sensitivity of oral swabs is only 22% with Xpert Ultra. 8 Other sampling methods include the Pediatric Entero-string test, which retrieves gastric fluid via a nylon string coiled in a swallowed capsule for TB testing.…”
Section: Sample Collection Methods In Children and Their Diagnostic A...mentioning
confidence: 99%
“…In search of an alternative non-sputum sample type, we and others have shown that MTB DNA can be detected by oral swab analysis (OSA) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In OSA, the dorsum of the tongue is brushed with a sterile swab, and the collected material is tested for MTB DNA.…”
Section: Introductionmentioning
confidence: 99%